Strategies to increase production efficiency in Indonesian Sharia commercial banks using Stochastic Frontier Approach (SFA) - Pratystya Ika Wardhani; Abdul Mongid (Universitas Hayam Wuruk Perbanas, 2018)
The purpose of this research is to examine the right strategy in increasing production efficiency in Sharia commercial banks in Indonesia. This research was conducted in two stages of testing. The first stage is estimating the level of production efficiency of Indonesian Islamic banks in 2010-2017 through the Stochastic Frontier Analysis (SFA) approach. The second stage uses Tobit regression to examine the relationship between the efficiency of production of sharia commercial banks with specific bank characteristics, including; LASSET, CAR, NPF, GCG, NOM and FDR. The results indicate that the level of production efficiency of sharia commercial banks is strongly influenced by several things. From the input side, optimization of DPK, PSC and LC components is needed to maximize production efficiency. This study also found that CAR (solvency performance), NPF (asset quality performance), NOM (profitability performance), and FDR (liquidity performance) greatly influenced variations in the efficiency of Indonesian Islamic banks. Improving the quality of financing supported by an increase in the operational system and the quality of human resources and began to concentrate on revenue sourced from services to be a solution that could be implied by Indonesian Islamic banks.